2022
DOI: 10.1038/s41423-022-00961-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular CIRP dysregulates macrophage bacterial phagocytosis in sepsis

Abstract: In sepsis, macrophage bacterial phagocytosis is impaired, but the mechanism is not well elucidated. Extracellular cold-inducible RNA-binding protein (eCIRP) is a damage-associated molecular pattern that causes inflammation. However, whether eCIRP regulates macrophage bacterial phagocytosis is unknown. Here, we reported that the bacterial loads in the blood and peritoneal fluid were decreased in CIRP−/− mice and anti-eCIRP Ab-treated mice after sepsis. Increased eCIRP levels were correlated with decreased bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…Infection is the major factor which directly causes death after radiation ( 3 , 4 ). We have recently shown that eCIRP suppresses macrophage bacterial phagocytosis by STAT3 phosphorylation followed by the formation of STAT3-βPIX complex, which leads to Rac-1 inhibition ( 29 ). Even though the role of TREM-1 was not assessed in that study, upregulation of TREM-1 by eCIRP after radiation exposure may impair the phagocytic function of macrophages, considering the involvement of the eCIRP-TREM-1 axis reported in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is the major factor which directly causes death after radiation ( 3 , 4 ). We have recently shown that eCIRP suppresses macrophage bacterial phagocytosis by STAT3 phosphorylation followed by the formation of STAT3-βPIX complex, which leads to Rac-1 inhibition ( 29 ). Even though the role of TREM-1 was not assessed in that study, upregulation of TREM-1 by eCIRP after radiation exposure may impair the phagocytic function of macrophages, considering the involvement of the eCIRP-TREM-1 axis reported in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that eCIRP, a critical DAMP, causes apoptosis inhibition and aging in neutrophils and demonstrated that eCIRP is the major, if not only, factor to inhibit neutrophil apoptosis and increase aged neutrophils in sepsis by using CIRP −/− mice. Considering that eCIRP circulates systemically, as evidenced by elevated levels in the blood during sepsis (7,36), aged neutrophils may be generated not only within the microenvironment but also in the circulation or remote organs. We have previously found that CIRP −/− mice were protected from multiple organ injuries and exhibited improved survival in sepsis (7,36).…”
Section: Discussionmentioning
confidence: 99%
“…CIRBP is induced by multiple external stimuli, including infection, hypoxia, hypothermia, and ultraviolet radiation, and it acts as a DAMP molecule that aggravates the inflammatory response 124,125 . Several studies have demonstrated that increased expression of CIRBP in the plasma predicts the poor prognosis of patients with sepsis 126,127 . In addition, it has been reported that increased expression of CIRBP can induce the expression of inflammatory cytokines by activating the NF‐kB and ERK signaling pathways 128–130 .…”
Section: Potential Role Of Rna Binding Proteins In Intervertebral Dis...mentioning
confidence: 99%